Cochrane Database of Systematic Reviews 2008
DOI: 10.1002/14651858.cd002295.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Exercise interventions for smoking cessation

Abstract: Background Taking regular exercise may help people give up smoking by moderating nicotine withdrawal and cravings, and by helping to manage weight gain. Objectives To determine whether exercise-based interventions alone, or combined with a smoking cessation programme, are more effective than a smoking cessation intervention alone. Search methods We searched the Cochrane Tobacco Addiction Group Specialized Register in April 2014, and searched MEDLINE, EMBASE, PsycINFO, and CINAHL Plus in May 2014. Selection cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(44 citation statements)
references
References 168 publications
2
39
0
3
Order By: Relevance
“…The impact of voluntary exercise on abstinence from drug use has been studied in humans with regard to nicotine [101103] and alcohol [104] addiction, with some of these studies indicating a beneficial effect. With regard to animal models of addiction, only a few studies have assessed whether exercise after the cessation of drug use can reduce the reinstatement of drug-seeking behavior [6163].…”
Section: Therapeutic Implications: Can Enhancing Neurogenesis Promotementioning
confidence: 99%
“…The impact of voluntary exercise on abstinence from drug use has been studied in humans with regard to nicotine [101103] and alcohol [104] addiction, with some of these studies indicating a beneficial effect. With regard to animal models of addiction, only a few studies have assessed whether exercise after the cessation of drug use can reduce the reinstatement of drug-seeking behavior [6163].…”
Section: Therapeutic Implications: Can Enhancing Neurogenesis Promotementioning
confidence: 99%
“…Although efforts to determine if exercise has beneficial effects in smoking-cessation programs have been mixed (see (Ussher et al, 2008) for review) one of the largest randomized controlled trials found beneficial effects up to 12 months after treatment (Marcus et al, 1999). Additionally, habitual exercisers that meet diagnostic criteria for exercise dependence smoked less than non-dependent exercisers (Lejoyeux et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the observed suppressive effects of wheel access on cocaine self-administration (Cosgrove et al, 2002; Smith et al, 2008; Smith et al, 2011) may depend on increasing the relative reward value of wheel activity over its value in wheel-naïve animals. This has implications for the use of exercise in drug-use cessation trials and perhaps may explain variability in outcome across trials (Ussher et al, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…The effect of ET on HDL cholesterol is modest and it is modulated by genetic factors [12]. As regards of smoke, only 1 out of 15 trials documented an effect of ET on smoking cessation [13], therefore it has only a complementary role in tobacco cessation programs.…”
Section: Benefits Of Exercise-based Cardiac Rehabilitation Programsmentioning
confidence: 99%